Re-Think the Strip: de-implementing a low value practice in primary care - Katrina E. Donahue; Marcella H. Boynton; Jennifer Leeman; Jennifer Rees; Erica Richman; Kathleen Mottus; Lisa P. Spees; Maihan B. Vu; April B. Reese; Hazel Tapp; Adam Lee; Asia Johnson; et al. (BMC Primary Care)
Abstract Background Self-monitoring of blood glucose (SMBG) is a low value health care practice that does not benefit most patients with non-insulin treated type 2 diabetes (T2DM). This paper evaluates Re-Think the Strip (RTS), a multi-component study aimed at de-implementing SMBG among non-insulin treated T2DM patients in primary care. Methods This study used a pre-post design to evaluate the effectiveness and implementation of Re-Think the Strip in 20 primary care clinics with a comparison group of 34 clinics within one health system. De-implementation strategies were implemented over 12 months and practices were followed for 18 months. Results There was an overall decrease in the odds of receiving a prescription for diabetes testing supplies (i.e., test strips and/or lancets) between the baseline and 12-month intervention follow-up for intervention and comparison clinics (OR 0.96, 95% CI 0.94, 0.98). However, there was no statistically significant difference in prescribing between the intervention and comparison clinics. In sensitivity analyses, a small intervention effect was observed for those patients newly diagnosed with T2DM or newly assigned to a study clinic (OR = 0.97, 95% CI 0.95, 1.00). Conclusions De-implementation strategies are feasible in primary care practices. Although prescriptions for SMBG decreased in intervention practices, they also decreased in the comparison practices. Newly diagnosed patients or new patients may be more receptive to de-implementation. Other factors, including the COVID-19 pandemic and baseline prescribing rates may have limited the effectiveness of the RTS de-implementation strategy.